Estimation of BLB (Bacterial Leaf Blight) Disease Attack Intensity in Rice Plant by the use of Thermal Imaging - Jullyantari, Ni Luh Putu; Wijaya, I Made Anom. S.; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Bacterial Leaf Blight (BLB) is a dangerous disease for rice plants. This disease can attack in every phase of growth. Calculation of BLB disease attack intensity is currently still done manually. Technology development in estimating the intensity of BLB disease is very necessary. This study aims to establish the equation for estimating BLB disease intensity using a thermal image approach. Drone DJI Inspire 1 with a thermal camera DJI Zenmuse XT was used in this research. Processing data using software Agisoft Photoscan, Arcgis 10.3 and Microsoft Excel. From the results of the thermal image analysis, it was found that the equation for estimating attack intensity is y = 4.9533x-144.42 and estimation accuracy is high at 90,45% with an error value of 8,43%. Temperature of the canopy can be classified into four according to the intensity of the attack, namely 29,83-31,84oC for mild attack intensity, 31,85-34,39oC for moderate attack intensity, 34,40-43,52oC for intensity of severe attacks and 43,53-48,09oC for intensity of puso attacks. From these results it can be concluded that the thermal image approach can be used to estimate BLB disease attacks on rice plants.